Final results from a defibrotide treatment‐IND study for patients with hepatic veno‐occlusive disease/sinusoidal obstruction syndrome. (16th May 2018) - Kernan, Nancy A.; Grupp, Stephan; Smith, Angela R.; Arai, Sally; Triplett, Brandon; Antin, Joseph H.; Lehmann, Leslie; Shore, Tsiporah; Ho, Vincent T.; Bunin, Nancy; Iacobelli, Massimo; Liang, Wei; et al.
Summary: Hepatic veno‐occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a potentially life‐threatening complication of haematopoietic stem cell transplant (HSCT) conditioning and chemotherapy. Defibrotide is approved for treatment of hepatic VOD/SOS with pulmonary or renal dysfunction [i.e., multi‐organ dysfunction (MOD)] after HSCT in the United States and severe VOD/SOS after HSCT in patients aged older than 1 month in the European Union. Defibrotide was available as an investigational drug by an expanded‐access treatment programme (T‐IND; NCT00628498). In the completed T‐IND, the Kaplan–Meier estimated Day +100 survival for 1000 patients with documented defibrotide treatment after HSCT was 58·9% [95% confidence interval (CI), 55·7–61·9%]. Day +100 survival was also analysed by age and MOD status, and post hoc analyses were performed to determine Day +100 survival by transplant type, timing of VOD/SOS onset (≤21 or >21 days) and timing of defibrotide treatment initiation after VOD/SOS diagnosis. Day +100 survival in paediatric patients was 67·9% (95% CI, 63·8–71·6%) and 47·1% (95% CI, 42·3–51·8%) in adults. All patient subgroups without MOD had higher Day +100 survival than those with MOD; earlier defibrotide initiation was also associated with higher Day +100 survival. The safety profile of defibrotide in the completed T‐IND study was similar to previous reports.